2011
DOI: 10.1186/1741-7007-9-2
|View full text |Cite
|
Sign up to set email alerts
|

Inland post-glacial dispersal in East Asia revealed by mitochondrial haplogroup M9a'b

Abstract: BackgroundArchaeological studies have revealed a series of cultural changes around the Last Glacial Maximum in East Asia; whether these changes left any signatures in the gene pool of East Asians remains poorly indicated. To achieve deeper insights into the demographic history of modern humans in East Asia around the Last Glacial Maximum, we extensively analyzed mitochondrial DNA haplogroup M9a'b, a specific haplogroup that was suggested to have some potential for tracing the migration around the Last Glacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 53 publications
(78 reference statements)
3
40
0
Order By: Relevance
“…3 However, the observed gene flow from northeast India suggests genetic contribution, albeit limited, from this region, a scenario echoing the proposed inland dispersal route. 50 In this spirit, our findings complete the understanding of the origin of the Nepalese and the way how the East Eurasian genetic components had been introduced into Nepal. Taking into account the previous observation on Y chromosome, 4 now it is convincing that the East Eurasian had entered Nepal across the Himalayas around 6 kya, a scenario in good agreement with the previous findings from linguistics and archeology.…”
Section: Reconstructing the Origin Of The Nepalese H-w Wang Et Alsupporting
confidence: 57%
See 1 more Smart Citation
“…3 However, the observed gene flow from northeast India suggests genetic contribution, albeit limited, from this region, a scenario echoing the proposed inland dispersal route. 50 In this spirit, our findings complete the understanding of the origin of the Nepalese and the way how the East Eurasian genetic components had been introduced into Nepal. Taking into account the previous observation on Y chromosome, 4 now it is convincing that the East Eurasian had entered Nepal across the Himalayas around 6 kya, a scenario in good agreement with the previous findings from linguistics and archeology.…”
Section: Reconstructing the Origin Of The Nepalese H-w Wang Et Alsupporting
confidence: 57%
“…49 Previous studies have observed substantial East Eurasian genetic components in the Nepalese populations; 4,5 however, it remains controversial whether the East Eurasian lineages have been introduced into Nepal from Tibet directly (across the Himalayas) 4,6 or via northeast India. 5,8,50 By extensively analyzing the mtDNA variation in Nepal, Tibet, northern India populations, our observations, based on the principle component analysis, Fst and admixture estimation, revealed the closer genetic affinity between the Nepalese and the Tibetans, and this result was further substantiated by the median networks, (Figures 4 and 5) in which most of the Nepalese mtDNAs prevalent among northern Asian populations shared the haplotypes with the Tibetans at root level or branched off directly from the nodes consisting almost exclusively of the Tibetan lineages. Our results strongly suggest that most of the East Eurasian maternal components identified in the Nepalese were introduced directly from Tibet, 4,6 and the time estimation results further date that this peopling scenario plausibly occurred about 6 kya.…”
Section: Reconstructing the Origin Of The Nepalese H-w Wang Et Almentioning
confidence: 99%
“…The derived EPAS1 haplotype was recently shown to have originated in the Denisova genome and its presence in the human genome represents a recent archaic introgression (36). Consequently, the subsequent selection of this haplotype in humans is difficult to model using genetic data from living populations, and dates ranging from 2,750 ya to 18,250 ya have been proposed (13,17,38).…”
Section: Resultsmentioning
confidence: 99%
“…Currently available archaeological and osteological data and genetic data from modern-day populations have been used to support contrasting hypotheses of South Asian (9-11), Central Asian (12), lowland Southeast Asian (13), and high-altitude East Asian (7,8) origins for the earliest Himalayan inhabitants, and there is likewise little agreement regarding subsequent regional population history (12,14). Successful permanent habitation of high-altitude environments requires numerous physiological adaptations, and recent genetic studies have identified robust signals of positive natural selection underlying adaptations to hypoxia in Tibetans (15)(16)(17) and in the Sherpa (18), an ethnic group that migrated from the eastern Tibetan plateau to Nepal 400-600 y ago (ya) (19).…”
mentioning
confidence: 99%
“…18,19 The Neolithic genetic components from Northern China were revealed to contribute substantially to the current gene pool of Tibetans. [18][19][20] Nevertheless, the susceptible alleles for LP in those surrounding populations were not introgressed into Tibetan populations via the prehistorical and historical migrations. Taken together, we propose that the LP in Tibetans is likely to have an independent origin.…”
mentioning
confidence: 99%